Controllability and observability of linear discrete-time fractional-order systems - Guermah, Said; Djennoune, Said; Bettayeb, Maamar (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we extend some basic results on the controllability and observability of linear discrete-time fractional-order systems. For both of these fundamental structural properties we establish some new concepts inherent to fractional-order systems and we develop new analytical methods for checking these properties. Numerical examples are presented to illustrate the theoretical results.
Keywords: system modeling; discrete fractional state-space systems; reachability; controllability; observability